Values, emotional states, happiness: contributions to corporate education - Ribeiro, Ivana de Campos; Pacheco, José Pedro Scarpel; Schwartz, Gisele Maria (Revista Hipótese, 2018)
This qualitative study aimed to reflect on the development of strategies involving emotional states and happiness of workers at public and privates corporations. The study explores the interdisciplinary scientific basis for happiness, emotional states, values and their interfaces with well-being, generating assumptions to consider the importance of reflections on self-knowledge as relevant to promote the organizational commitment.
Keywords: Well-being; emotional states; sustainability; values; happiness